1994
DOI: 10.1002/j.1460-2075.1994.tb06331.x
|View full text |Cite
|
Sign up to set email alerts
|

A dominant negative mutation in the conserved RNA helicase motif ‘SAT’ causes splicing factor PRP2 to stall in spliceosomes.

Abstract: To characterize sequences in the RNA helicase‐like PRP2 protein of Saccharomyces cerevisiae that are essential for its function in pre‐mRNA splicing, a pool of random PRP2 mutants was generated. A dominant negative allele was isolated which, when overexpressed in a wild‐type yeast strain, inhibited cell growth by causing a defect in pre‐mRNA splicing. This defect was partially alleviated by simultaneous co‐overexpression of wild‐type PRP2. The dominant negative PRP2 protein inhibited splicing in vitro and caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 53 publications
1
86
0
1
Order By: Relevance
“…Such an approach has been successfully applied to precisely determine the function of many RNA helicases in energy-dependent steps of spliceosome assembly-disassembly. In almost all cases, these proteins were trapped in inactive spliceosomes (2,10,19,26,31,39,40). This strategy has also been adapted to characterize the recently discovered Q motif (44).…”
Section: Fig 1 (A)mentioning
confidence: 99%
See 2 more Smart Citations
“…Such an approach has been successfully applied to precisely determine the function of many RNA helicases in energy-dependent steps of spliceosome assembly-disassembly. In almost all cases, these proteins were trapped in inactive spliceosomes (2,10,19,26,31,39,40). This strategy has also been adapted to characterize the recently discovered Q motif (44).…”
Section: Fig 1 (A)mentioning
confidence: 99%
“…The first aspartic acid in motif II (DEXD/H box), which may coordinate binding of the Mg 2ϩ cofactor (3), was replaced by alanine. The first amino acid in motif III was mutated to a leucine, which, based on in vivo and in vitro studies, may uncouple ATP hydrolysis and RNA helicase activity (30,31,40). Overall, we predicted that these mutations would specifically affect ATP binding and hydrolysis and would have the lowest probability of affecting RNA or RNP substrate binding.…”
Section: Vol 26 2006 Mutational Analysis Of Dexd/h Box Rna Helicasementioning
confidence: 99%
See 1 more Smart Citation
“…Important information concerning the 59SS:hPrp28p interaction was obtained from the mapping of the site of crosslink within the protein+ Because of the remarkable specificity of the BP-mediated crosslinking, the resulting product is virtually homogenous, representing a single contact between the 59SS RNA and hPrp28p+ The crosslink site maps to a short segment in the helicase domain of hPrp28p (amino acid positions 601-609), spanning the conserved TAT motif (motif III, positions 606-608; Lüking et al+, 1998)+ Mutational studies suggested that motif III (which in many other DExD/Hbox proteins contains an SAT rather than TAT sequence) is involved in coupling ATP hydrolysis with duplex unwinding (Schwer & Guthrie, 1992;Plumpton et al+, 1994;Gross & Shuman, 1998)+ In fact, in several DExH-box proteins, mutations of this motif result in inhibition of splicing (Plumpton et al+, 1994; B+ Schwer, pers+ comm+)+ Based on the structural similarity of several helicases, including PcrA and Rep DNA helicases (Subramanya et al+, 1996;Korolev et al+, 1997) and HCV RNA helicase (Yao et al+, 1997), a unifying mechanism for this class of proteins has been suggested (Bird et al+, 1998)+ Helicases coordinate a cycle of ATP binding and hydrolysis to an ordered series of conformational changes that allow the protein to move along its substrate+ Because of its localization in a hinge region connecting the two protein domains, motif III is thought to play a pivotal role in these conformational changes+ The current models predict that, upon binding of ATP and the single stranded portion of the substrate, the protein assumes a closed conformation+ Subsequent ATP hydrolysis yields an opened conformation of the protein, resulting in a stretched motion that pulls the single strand of RNA (or DNA) and as a result, unwinds the substrate duplex+ The structural organization of helicases requires that during catalysis, the single-stranded substrate is positioned in proximity of the conserved motif III hinge connecting the two protein domains that undergo the ATP-dependent conformational changes (Bird et al+, 1998;Velankar et al+, 1999)+ Although the structure of hPrp28p is not currently known, its TAT motif most likely also connects the two conformationally changing domains of the protein+ If the position of the single-stranded RNA relative to motif III is similar in hPrp28p and HCV NS3 RNA helicase, the observed BP-mediated crosslink (;15 Å linker) between the 59SS RNA and the TAT motif of hPrp28p is fully consistent with the predicted structure, strongly suggesting that the 59SS represents a true substrate for hPrp28p+ Although it is formally possible that the observed 59SS:hPrp28p crosslink reflects only a close proximity, and not the direct contact between the 59SS and the helicase, the simplest interpretation is that the crosslink results from the proper positioning of the 59SS in the opened conformation of hPrp28p+ In fact, the present study offers the first biochemical evidence of the direct, specific contact between an RNA substrate and its putative RNA helicase+…”
Section: Location Of the 59ss Rna Crosslink Within Hprp28pmentioning
confidence: 99%
“…The DEAD/DEXH-box proteins are involved in diverse cellular functions including pre-mRNA splicing (Wassarman & Steitz, 1991;Ripmaster et al+, 1992;Schmid & Linder, 1992;Czaplinski et al+, 1995;Liang et al+, 1996;Margossian et al+, 1996;Ohno & Shimura, 1996;Py et al+, 1996;Chuang et al+, 1997)+ This family is characterized by several highly conserved ATPase motifs including the DEAD or DExH sequence (Chang et al+, 1990;Koonin, 1991;Bork & Koonin, 1993)+ Functional assignments for several of the motifs have been made through analyses of various RNA helicases, including the extensively studied eIF4A (Pause & Sonenberg, 1992;Pause et al+, 1993Pause et al+, , 1994+ Mutations in ATPase A motif (GKT, motif I) affect ATP binding, whereas mutations in ATPase motif B (DEAD or DExH, motif II) affect ATP hydrolysis+ Motif VI (GRAGR) is involved in ATP hydrolysis, and the SAT sequence element (motif III) is essential for RNA unwinding+ Mutational alterations in these motifs result in specific functional impairment of each helicase thus far studied (Ohno & Simura, 1996;Burgess & Guthrie, 1993;Plumpton et al+, 1994)+ Analysis of dominant negative mutations has been proposed as a tool for identifying the function of a gene product by observing the functional and biochemical consequences of overexpressing mutant proteins in the presence of the wild-type protein (Herskowitz, 1987)+ It has been suggested that the generation of dominant negative mutations that affect the ATPase domains of DEAD or DExH proteins could provide a powerful strategy for elucidating the diverse roles of this gene/ protein family (Schwer & Guthrie, 1992b)+ Several dominant negative mutants in ATPase domains have been created to investigate the function of DEAD/Hbox proteins (Schwer & Guthrie, 1992b;Burgess & Guthrie, 1993;Plumpton et al+, 1994;Ohno & Simura, 1996;Kim & Lin, 1996)+ Studies of mutations in pre-mRNA splicing factors PRP2 and PRP16 have shown that mutant proteins with reduced ATPase activity remain tightly bound to their spliceosomal substrate (Schwer & Guthrie, 1992b;…”
Section: Introductionmentioning
confidence: 99%